As ciências sociais e a transição democrática no Brasil - Prado, João Victor Bessa (2021)
We start this research from the hypothesis that the debates promoted by the Brazilian Social Sciences throughout the period of the democratic transition, were situated around the themes of the parties ideological consolidation, and the growth of channels for popular participation in the decision-making spaces. To investigate them, we defined three fundamental institutions (along with their journals) to think about the Social Sciences presence in the redemocratization process: CEBRAP (through the journal Novos Estudos CEBRAP), CEDEC (through the journal Lua Nova) and ANPOCS (through the RBCS and BIB journals). Through the political history of foucaultian provenance, we bulid the first chapter by merging the relations between intellectuals and the State throughout the 20th century, pointing out to different interpretations of democracy: that of anarchists, authoritarian jurists (1920-1930), of the developmentalists (1950-1960) and social scientists (1970-1980). Departing from Foucault's archeology, in the second chapter we analyze the articles in the aforementioned magazines, selected to monitor which kind of democracy the intellectuals aspired for the country’s future. Totaling thirty nine articles, the analysis partially confirmed the hypotheses, since, despite the themes emergence, more specific issues gained greater prominence in the debate, such as the civil society’s participation and the National Constituent Assembly responsibilities, and less that of the parties, within the transition’s process